Rashwani, Samer Abdul-Rahman. “The Maqāṣidī Trend in the Exegesis of Ibn ʿĀshūr,” Year 6, Issue 23 (Winter 1421 AH/ 2000 CE), Pp. 81-107. - رشواني سامر عبد الرحمن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2000)
After defining the tafsīrī (exegesis) trend and the interpretation of “liberation” and “enlightenment” (taḥrīr and tanwīr, respectively), Samer Rashwani discusses the maqāṣidī (purposiveness) trend in Ibn ʿĀshūr’s exegesis of the Qur’an on the theoretical level, addressing its tendency towards critique and renewal, the nature of the trend, and how it is distinguished from the hidā’ī (guidance) trend. In the second part of his article, he addresses practical application and discusses the purposiveness behind texts, providing a few examples including the matter of dispensation granted in tayammum (dry ablution); and he discusses inference from evidence and legal rulings. In the third part of his article, he addresses features of Ibn ʿĀshūr’s methodology in his exegesis, before concluding with a summary highlighting the main results of his research.